(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluate the results of treatment for lumbar disc herniation using endoscopic surgery by the interlaminar approach at Thai Nguyen Central Hospital. Subjects and methods: A cross-sectional descriptive study of 33 patients was diagnosed with single-level lumbar disc herniation who were operated endoscopy by the interlamina approach, between 01/2021 and 12/2023 at Thai Nguyen Central Hospital. Results: Among the 33 cases of disc herniation treated with endoscopic interlaminar surgery, there were 20 males and 13 females. The average age of the study group was 46.09 years. The highest occupational rate was in heavy labor (42.4%). The average surgery time was 79.39 minutes, and the average postoperative hospital stay was 3.45 days. Postoperative leg and back pain significantly improved, with average pain scores of 5.4 and 3.91, respectively, showing a statistically significant difference with p < 0.05. The average postoperative ODI (Oswestry Disability Index) score was 17.28, a marked improvement from the preoperative score of 62.03. Very good results were observed in 69.7% of cases, and good results in 30.3%. At discharge, the rates of very good and good results were 90.9% and 9.1%, respectively. Conclusion: Endoscopic interlaminar surgery for single-level lumbar disc herniation at Thai Nguyen Central Hospital has shown very good early outcomes. This procedure is safe and effective, and it should be maintained and widely applied.